ANALISIS PERAMALAN EKSPOR BESI ATAU BAJA DARI INDONESIA KE SINGAPURA DENGAN METODE TIME SERIES - Wiguna Wiguna (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Exporting iron or steel is a crucial sector for Indonesia's economy, and Singapore is one of its main trading partners in terms of exporting these products. In order to optimize the performance of iron or steel exports to Singapore, a deep understanding of the trends and patterns present in export data is necessary. Therefore, forecasting analysis using time series methods is highly relevant and required. The methodology used in this study is a descriptive-analytical method with data collection from secondary sources. The population consists of iron or steel exports from Indonesia to Singapore, with a sample comprising export data from 2017 to 2021, and the sample determination technique uses the purposive sampling method. The data analysis techniques used are descriptive statistical methods and time series forecasting. The research results indicate that the export of iron or steel from Indonesia to Singapore has shown a positive trend over the past five years, influenced by factors such as strong demand, resource availability, developing infrastructure, product quality, and so on. Based on the forecasting analysis, it is estimated that the demand for iron or steel from Indonesia to Singapore in the coming years will continue to increase. The findings of this research provide valuable insights for the players in the iron or steel industry in Indonesia, especially exporters and stakeholders in the supply chain. With accurate forecasting, production and delivery planning can be optimized, market trends can be identified, and demand fluctuations in Singapore can be anticipated.